2022
DOI: 10.3390/ani12131604
|View full text |Cite
|
Sign up to set email alerts
|

High Dietary Organic Iron Supplementation Decreases Growth Performance and Induces Oxidative Stress in Broilers

Abstract: Although Iron (Fe) is an essential nutrient that plays a vital role in respiratory processes, excessive Fe in the diet can affect the health of broilers. We investigated the effects of diet supplemented with high levels of iron chelates with lysine and glutamic acid (Fe–LG) on the growth performance, serum biochemical parameters, antioxidant status, and duodenal mRNA expression of Fe transporters in broilers. A total of 800 1-day-old male Arbor Acres broilers were assigned to 5 groups, with 8 replicates each. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 60 publications
1
5
0
Order By: Relevance
“…In our study, the serum, liver, and muscle MDA levels were not affected by the IONP supplementation. Our results are in line with the study conducted by Han et al [ 34 ], who reported no changes in the serum and liver MDA levels in broilers supplemented with iron chelated with lysine and glutamine. Iron nanoparticle supplementation decreased the hepatic MDA levels in broilers subjected to heat stress, indicating the antioxidant potential of IONPs, and suggesting the need for IONP supplementation during heat stress conditions [ 28 ].…”
Section: Discussionsupporting
confidence: 93%
“…In our study, the serum, liver, and muscle MDA levels were not affected by the IONP supplementation. Our results are in line with the study conducted by Han et al [ 34 ], who reported no changes in the serum and liver MDA levels in broilers supplemented with iron chelated with lysine and glutamine. Iron nanoparticle supplementation decreased the hepatic MDA levels in broilers subjected to heat stress, indicating the antioxidant potential of IONPs, and suggesting the need for IONP supplementation during heat stress conditions [ 28 ].…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, glutamate can prevent ferroptosis by chelating iron. 45 In addition, exogenous GSH supplementation can alleviate the depletion of GSH, play an antioxidant role, and slow down the process of ferroptosis to a certain extent. 18 Ferrostatin-1 is a synthetic antioxidant, which can prevent the damage of the membrane lipid through the reduction mechanism, ultimately restraining ferroptosis.…”
Section: Resultsmentioning
confidence: 99%
“…Adenosine triphosphate (ATP), adenosine diphosphate (ADP), and tris­(2-carboxyethyl) phosphine (TCEP) have been proved to be able to adsorb iron, resulting in a deficiency of iron, which is indispensable in ferroptosis, and thereby inhibiting ferroptosis and weakening the bactericidal effect. Similarly, glutamate can prevent ferroptosis by chelating iron . In addition, exogenous GSH supplementation can alleviate the depletion of GSH, play an antioxidant role, and slow down the process of ferroptosis to a certain extent .…”
Section: Resultsmentioning
confidence: 99%
“…Increased hepatic ferritin expression suggests that this is the major storage protein of Fe ( Basclain et al, 1998 ), and, therefore, the parallel increases of ferritin and liver Fe are expected. It seems that an upper limit for Fe storage in the liver is out of range in commercial type diets ( Ma et al, 2016 ; Akter et al, 2017 ; Han et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%